Service Excellence, Product Quality, and Facilities as Drivers of Customer Satisfaction: Evidence from Warkop Icut Kuliner, Binjai - Ali Topan; Mesra B (Lembaga Riset dan Inovasi Al-Matani, 2025)
This study was conducted at Warkop Icut Binjai to examine the effect of service quality, product quality, and facilities on consumer satisfaction. The population consisted of 90 consumers of Warkop Icut Kuliner Binjai. The sampling method used was saturated sampling, resulting in a total of 90 respondents. Data were analyzed using multiple linear regression, classical assumption tests, and hypothesis testing. The results show that service quality, product quality, and facilities have both partial and simultaneous positive and significant effects on consumer satisfaction. There is a strong correlation between service quality, product quality, and facilities and consumer satisfaction at Warkop Icut Binjai. Consumer satisfaction at Warkop Icut can be explained by service quality, product quality, and facilities by 34.3%, while the remaining 65.7% is explained by other variables not examined in this study.